INHERITANCE OF NITRATE REDUCTASE ACTIVITY IN Zea mays L - Warner, Robert L. (1969)
Since the F(1) hybrid (B14 × Oh43) had been shown to have a higher (heterotic) level of nitrate reductase activity than either inbred parent (B14 or Oh43), studies were undertaken to determine the mode of inheritance. Standard methods for determining Mendelian inheritance were used to study segregation for level of nitrate reductase activity of individual plants. The genetic material used was the inbreds B14 and Oh43, F(1), F(1) backcrossed to both parents, F(2), F(3), and F(4) generations of the cross B14 × Oh43. The plant material was grown in the field and in growth chambers. It was shown that the maize inbreds B14 and Oh43 differ at two loci that control the level of nitrate reductase activity. Each inbred is homozygous for a dominant or partially dominant allele at one locus and homozygous recessive at a second locus. The locus at which B14 carries a dominant allele carries the recessive allele in Oh43. Oh43 has both a higher in vivo rate of synthesis of nitrate reductase and higher in vivo and in vitro loss of enzyme activity (decay) than B14. Thus, the rates of both enzyme synthesis and decay are factors governing the level of nitrate reductase activity in corn. The data suggest that the heterotic level of nitrate reductase activity in the F(1) hybrid is the result of inheritance of qualities that gives it “intermediate” rates of enzyme synthesis and decay.